Financial Exploitation of Older Adults: A Population-Based Prevalence Study - Peterson, Janey C. (J Gen Intern Med, 2014)
BACKGROUND: Financial exploitation is the most common and least studied form of elder abuse. Previous research estimating the prevalence of financial exploitation of older adults (FEOA) is limited by a broader emphasis on traditional forms of elder mistreatment (e.g., physical, sexual, emotional abuse/neglect). OBJECTIVES: 1) estimate the one-year period prevalence and lifetime prevalence of FEOA; 2) describe major FEOA types; and 3) identify factors associated with FEOA. DESIGN: Prevalence study with a random, stratified probability sample. PARTICIPANTS: Four thousand, one hundred and fifty-six community-dwelling, cognitively intact adults age ≥ 60 years. SETTING: New York State. MAIN MEASURES: Comprehensive tool developed for this study measured five FEOA domains: 1) stolen or misappropriated money/property; 2) coercion resulting in surrendering rights/property; 3) impersonation to obtain property/services; 4) inadequate contributions toward household expenses, but respondent still had enough money for necessities and 5) respondent was destitute and did not receive necessary assistance from family/friends. KEY RESULTS: One-year period FEOA prevalence was 2.7 % (95 % CI, 2.29–3.29) and lifetime prevalence was 4.7 % (95 % CI, 4.05–5.34). Greater relative risk (RR) of one-year period prevalence was associated with African American/black race (RR, 3.80; 95 % CI, 1.11–13.04), poverty (RR, 1.72; 95 % CI, 1.09–2.71), increasing number of non-spousal household members (RR, 1.16; 95 % CI, 1.06–1.27), and ≥ 1 instrumental activity of daily living (IADL) impairments (RR, 1.69; 95 % CI, 1.12–2.53). Greater RR of lifetime prevalence was associated with African American/black race (RR, 2.61; 95 % CI, 1.37–4.98), poverty (RR, 1.47; 95 % CI, 1.04–2.09), increasing number of non-spousal household members (RR, 1.16; 95 % CI, 1.12–1.21), and having ≥1 IADL (RR, 1.45; 95 % CI, 1.11–1.90) or ≥1 ADL (RR, 1.52; 95 % CI, 1.06–2.18) impairment. Living with a spouse/partner was associated with a significantly lower RR of lifetime prevalence (RR, 0.39; 95 % CI, 0.26–0.59) CONCLUSIONS: Financial exploitation of older adults is a common and serious problem. Elders from groups traditionally considered to be economically, medically, and sociodemographically vulnerable are more likely to self-report financial exploitation.